The Effect of Internal Locus of Control and Spiritual Intelligence on Personal Financial Management Behavior - Dewi Rahmayanti (Integrated Journal of Business and Economics (IJBE), 2023)
This study examines the effect of internal locus of control and spiritual intelligence on personal financial management behavior in Bengkulu, Indonesia. Snowball sampling was employed with a total sample size of 300 respondents. The data collection was collected through an online questionnaire distributed to the respondents using social media. The data was analyzed using SPSS to identify the relationship between variables. The results showed that internal locus of control has a positive effect on personal financial management behavior, spiritual intelligence has a positive effect on personal financial management behavior. Internal locus of control and Spiritual intelligence will shape better financial management behavior and reduce the possibility of financial stress in the future.